One size (doesn’t) fit all: new metaphors for and practices of scaling from indigenous peoples of the Northwest Amazon - Shaw, Kurt; da Silva, Rita de Cacia Oenning (Frontiers in Public Health, 2023)
Ten years of field research and collaborative development of programs for early childhood in the Upper Rio Negro region of the Amazon provide the authors with new metaphors for achieving wider social impact and new frames to add to the international debate on ‘scaling’ social change initiatives. Using anthropology and ethno-ontology to think questions of universal and particular, center and periphery, the article reflects on the dangers of monolithic scaling to cultural diversity and future innovation. Instead of the metaphor of scaling — adopted in the discourse of public policy and international development from the Fordist or Taylorist efficiency of the economy of scale — indigenous people speak of exchange, sharing, and transformation. These ideas seek to connect local and decolonized models and value the diversity of local knowledges, epistemologies, and practices around early childhood development. Based on the expansion of the CanalCanoa project among diverse indigenous communities, the paper proposes a flexible and bottom-up model of achieving impact at scale through empowering local actors to teach each other and establish local criteria of learning and evaluation.